2020
DOI: 10.3390/w12082205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Water Balance Variables under Land Use and Climate Projections in the Upper Choctawhatchee River Watershed, in Southeast US

Abstract: Changes in water balance variables are essential in planning and management. Two major factors affecting these variables are climate change and land use change. Few researches have been done to investigate the combined effect of the land use change and climate change using projections. In this study the hydrological processes in Upper Choctawhatchee River Watershed were modeled using the Soil and Water Assessment Tool (SWAT) to investigate the impacts of climate and land use change. We integrated land use proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 118 publications
0
9
0
1
Order By: Relevance
“…The well-known components of water balance are surface runoff, ground water, lateral flow, water yield, and evapotranspiration [43,56,57]. According to the findings, it was observed that more than 80% and 40% of the surface runoff and ground water occurs during the wet season for all LULC time periods, while less than 10% of the surface runoff occurs during the dry and short rainy seasons (Figure 8).…”
Section: Model Efficiencymentioning
confidence: 93%
“…The well-known components of water balance are surface runoff, ground water, lateral flow, water yield, and evapotranspiration [43,56,57]. According to the findings, it was observed that more than 80% and 40% of the surface runoff and ground water occurs during the wet season for all LULC time periods, while less than 10% of the surface runoff occurs during the dry and short rainy seasons (Figure 8).…”
Section: Model Efficiencymentioning
confidence: 93%
“…The minor reduction in mean streamflow is due to the fewer urban areas in 1995 and 2005 compared to the historical period (Table 3). Urbanization is the primary factor increasing the streamflow due to increasing impervious areas (Aghsaei et al, 2020;Makhtoumi et al, 2020). Furthermore, some studies have reported similar conclusions (Nie et al, 2011;Yan et al, 2013).…”
Section: Results and Discussion Calibration And Validationmentioning
confidence: 83%
“…The seasonal responses to land-use change for flow and sediment have been emphasized due to enormous alterations, such as urbanization and agricultural expansion [51]. Land-use changes have increased the risk of extreme hydrological circumstances, including flooding and drought events [12].…”
Section: Influence Of Land-use Update For Flow and Sediment Simulationmentioning
confidence: 99%
“…The soil and water assessment tool (SWAT) has been widely applied for modeling watershed hydrology and simulating the movement of non-point-source pollution. In the existing studies on SWAT modeling, the impacts of land-use changes on runoff and sediment [10,11], water balances [12], hydrological processes [13], and streamflow characteristics [14] have already been analyzed by using a single static land-use input condition…”
Section: Introductionmentioning
confidence: 99%